Head First design patterns building extensible and maintainable object-oriented software - Freeman, Eric 1965-; Robson, Elisabeth; Sierra, Kathy; Bates, Bert (O'Reilly, 2020)
You know you don't want to reinvent the wheel, so you look to Design Patterns-- the lessons learned by those who've faced the same software design problems. With Design Patterns, you get to take advantage of the best practices and experience of others so you can spend your time on something more challenging. Something more fun. This book shows you the patterns that matter, when to use them and why, how to apply them to your own designs, and the object-oriented design principles on which they're based. Join hundreds of thousands of developers who've improved their object-oriented design skills through Head First Design Patterns.
Previous edition: Sebastopol, California: O'Reilly, 2004
Keywords: Java (Computer program language); Computer software -- Development; Object-oriented methods (Computer science); Software patterns; Java (Langage de programmation); Conception orientée objet (Informatique); Logiciels; Modèles de conception; Computer software; Development